2018
DOI: 10.3389/fcimb.2018.00235
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus Extracellular Adherence Protein Eap Is a DNA Binding Protein Capable of Blocking Neutrophil Extracellular Trap Formation

Abstract: The extracellular adherence protein (Eap) of Staphylococcus aureus is a secreted protein known to exert a number of adhesive and immunomodulatory properties. Here we describe the intrinsic DNA binding activity of this multifunctional secretory factor. By using atomic force microscopy, we provide evidence that Eap can bind and aggregate DNA. While the origin of the DNA substrate (e.g., eukaryotic, bacterial, phage, and artificial DNA) seems to not be of major importance, the DNA structure (e.g., linear or circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…Four of the ribosomal proteins and an additional two nonribosomal cytoplasmic proteins in the list (see the Foulston et al column in Table S1) were previously identified as being part of the biofilm matrix by the studies that led to the development of the electrostatic net model (33, 34), indicating that the proteins identified by the SW technique also corroborated approximately 20% of the cytoplasmic proteins identified in this study. Importantly, a number of proteins known to bind DNA were identified, including Atl (bands 1, 8, and 9) (36), SarA (band 5) (37), IsaB (band 5) (38), Eap (band 1) (39), and the phenol-soluble modulins (PSMs; band 11) (40). Interestingly, in the case of PSMs, it was further shown that the binding of PSMs to DNA protected the DNA from digestion by DNase (40), and in the case of Eap, it was found that this protein can condense extended DNA strands (39), raising the possibility that Eap might also afford protection from host DNase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the ribosomal proteins and an additional two nonribosomal cytoplasmic proteins in the list (see the Foulston et al column in Table S1) were previously identified as being part of the biofilm matrix by the studies that led to the development of the electrostatic net model (33, 34), indicating that the proteins identified by the SW technique also corroborated approximately 20% of the cytoplasmic proteins identified in this study. Importantly, a number of proteins known to bind DNA were identified, including Atl (bands 1, 8, and 9) (36), SarA (band 5) (37), IsaB (band 5) (38), Eap (band 1) (39), and the phenol-soluble modulins (PSMs; band 11) (40). Interestingly, in the case of PSMs, it was further shown that the binding of PSMs to DNA protected the DNA from digestion by DNase (40), and in the case of Eap, it was found that this protein can condense extended DNA strands (39), raising the possibility that Eap might also afford protection from host DNase.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, a number of proteins known to bind DNA were identified, including Atl (bands 1, 8, and 9) (36), SarA (band 5) (37), IsaB (band 5) (38), Eap (band 1) (39), and the phenol-soluble modulins (PSMs; band 11) (40). Interestingly, in the case of PSMs, it was further shown that the binding of PSMs to DNA protected the DNA from digestion by DNase (40), and in the case of Eap, it was found that this protein can condense extended DNA strands (39), raising the possibility that Eap might also afford protection from host DNase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that S. aureus extracellular protein Eap shows a neutrophil serine protease inhibitor activity in association with NET functions (49) and binds and aggregates DNA, thus blocking neutrophil extracellular trap formation (50). With this study, FnBPB is added to the list of potential factors that inhibit this important mechanism of host innate defense.…”
Section: Interactions Of Histones With S Aureus Fnbpbmentioning
confidence: 99%
“…S1), suggesting two possibilities, that Eap and SasG interact with and protect eDNA from nucleases and that the importance of eDNA is masked by these proteins. Recently, it was reported that Eap can bind to DNA and is capable of blocking neutrophil extracellular trap (NET) formation (44). However, the DNA binding capacity of SasG has not yet been elucidated.…”
mentioning
confidence: 99%